Cross-cultural adaptation and measurement properties of the Dutch knee self efficacy scale (K-SES) - Wim van Lankveld; Nicky van Melick; Bas Habets; Yvette Pronk; J. Bart Staal; Robert van Cingel (BMC, 2019)
Abstract Background Self-efficacy is related to outcome after anterior cruciate ligament (ACL) tears. The Knee Self Efficacy Scale (K-SES) available in Swedish and English, was developed to measure self-efficacy in present (K-SESpresent) and future (K-SESfuture) functioning. The objective of this study was to determine measurement properties of the K-SES in Dutch patients. Methods The K-SES was translated and structural validity, internal consistency, test-retest reliability, and measurement error were assessed in three patient samples: one group completed the questionnaire and additional measures pre-surgery (N = 200), and one group post-surgery (N = 58). The third group (post-surgery) completed the K-SES twice (N = 50). Results Exploratory factor analysis distinguished two underlying important factors: K-SESpresent and K-SESfuture. However, the distinction was not confirmed in Confirmatory Factor Analysis (CFA). Internal consistency for both subscales was excellent (Cronbach's alpha > .80). Test-retest reliability absolute agreement was 0.95. A-priori formulated hypotheses on the relation between Knee Self Efficacy Scale Dutch (K-SES-D) and related constructs were confirmed. Moderate to high correlations (r > 0.50) were reported with Knee Injury and Osteoarthritis Outcome Score (KOOS) before reconstruction. High negative correlation was found with fear of movement and pain catastrophizing (r < − 0.60), and low correlation (r < 0.50) with locus of control and measures of distress. Conclusion Acceptability, internal consistency and test-retest reliability of the K-SES-D subscales are satisfactory. Construct validity of both subscales was confirmed by exploratory factor analysis and hypothesis testing. However, construct validity was not confirmed in CFA. Further research is needed to test responsiveness.